URGENSI PENDIDIKAN ISLAM DALAM KONTEKS MULTIKULTURALISME - Ansori; Rika Putri Yanti; M. Shahid Anggi ER; Kasful Anwar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Islamic education plays a strategic role in fostering awareness and tolerance within multicultural societies such as Indonesia. Amid the diversity of ethnicities, religions, cultures, and languages, conflicts based on ethnic and religious differences (SARA) still frequently occur due to a lack of understanding of pluralistic values. Islamic education is not only aimed at shaping a religious personality but also at strengthening human values, tolerance, and social justice. Through a multicultural approach, Islamic education is expected to nurture an inclusive, humanistic, and democratic generation. This study seeks to explore the urgency and contributions of Islamic education in responding to the challenges of pluralism and to offer applicable strategies rooted in universal Islamic values to strengthen social cohesion amidst diversity.